Sustaining Weight Loss in Women: The Role of Social Intelligence and Physiotherapy in Optimizing Low Impact Aerobic Exercise and Pilates - Syurrahmi, Syurrahmi; Rahmanti, Ainnur; Margiyati; Dayaningsih, Diana; Krisna Dwi Patrisia, Ni Kadek (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2025)
The global rise in obesity necessitates effective interventions, particularly for women, who often face unique challenges. This study investigates the comparative effects of low-impact aerobic exercise and Pilates on body fat percentage reduction in obese women, considering the moderating role of age. A quantitative experimental design with pre- and post-tests was employed, involving 40 obese women recruited through purposive sampling. Participants engaged in either low-impact aerobic exercise or Pilates for eight weeks, with body fat percentage measured using skinfold calipers. Two-way ANOVA was used to analyze the data, revealing significant differences between exercise types and age groups. Low-impact aerobics demonstrated a greater reduction in body fat percentage compared to Pilates. Adolescents experienced a more pronounced reduction with aerobics, while adults benefited more from Pilates. These findings highlight the importance of tailoring exercise interventions to age-specific needs. Furthermore, social intelligence, motivation, adherence, and social support were identified as crucial factors in program success. This study underscores the potential of integrating social and psychological elements into physiotherapy practices to enhance weight management outcomes in obese women. The results provide valuable insights for designing targeted exercise programs that consider both physical and social-emotional factors.